Layered sheet and its manufacturing method, printed matter, and molded product

JP2025025156AActive Publication Date: 2025-02-21KURARAY CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2023129664
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-09
Publication Date
2025-02-21
Estimated Expiration
2043-08-09

AI Technical Summary

Benefits of technology

【0014】 本開示によれば、インクジェット印刷用及び/又はレーザー切削加工用等として好適で、持続可能性に優れた積層シートを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025025156000001_ABST
    Figure 2025025156000001_ABST
Patent Text Reader

Abstract

To provide a layered sheet that is suitable for inkjet printing and / or laser cutting and the like, and has excellent sustainability.SOLUTION: A layered sheet (16X) of the present disclosure has: a base layer (21); and a surface layer (31) laminated on at least one side of the base layer (21), wherein the base layer (21) comprises a methacrylate resin (M) containing 80-100 mass% of a methyl methacrylate unit. The surface layer (31) comprises acrylonitrile-styrene copolymer (AS-E) having an elution time of 9 to 23 minutes at a peak top of a maximum peak in the chromatogram, wherein: a ratio of a copolymer of a composition whose elution time is less than 9 minutes is 0 to 5 mass% when a gradient high-performance liquid chromatography analysis is performed using two liquids, n-hexane and chloroform, as an eluent; and a ratio of a copolymer of a composition whose elution time is 23 minutes or longer is 0 to 5 mass%.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a laminated sheet, a manufacturing method thereof, a printed matter, and a molded article. [Background technology]

[0002] Inkjet printing, which can process digital images on a print medium using a computer, is becoming more and more popular as more types of printable media are being used. For example, it is now widely used in a variety of fields, including printing, advertising, sign displays, events, amusement, architecture, and interior design. Resin sheets are an example of a printing medium other than paper. Unlike paper, resin sheets are highly water-resistant and durable, and can also be made transparent.

[0003] After inkjet printing, the resin sheet for inkjet printing can be cut using a laser and an NC router, etc., as necessary, to form it into a desired shape. The molded product thus obtained can be preferably used for miscellaneous goods and fixtures such as key holders. A method for cutting a resin sheet using a laser is disclosed in claim 1 of Patent Document 1, for example. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2016-055348 A [Patent Document 2] JP 2018-094843 A [Patent Document 3] JP 2021-160119 A Summary of the Invention [Problem to be solved by the invention]

[0005] In applications such as miscellaneous goods and fixtures such as key holders, methacrylic resins are preferably used as the base resin of the resin sheet for inkjet printing from the viewpoints of transparency, ink color development, etc. As the ink for inkjet printing, ultraviolet (UV) curable inks and the like are preferably used. Examples of resins with good adhesion to inkjet printing ink include styrene copolymers. Patent Documents 2 and 3 disclose laminated sheets having a base layer containing a methacrylic resin and a surface layer containing a styrene copolymer such as a methyl methacrylate-styrene copolymer (MS resin), and suitable for use in inkjet printing, etc. (Claim 1 in Patent Document 2, Claim 1 in Patent Document 3).

[0006] In general, in the production of (co)extrusion molded sheets and molded products using the same, there are defective products that arise when the extrusion molding production line is started up, scraps generated by trimming both ends of the sheet, defective products that are determined not to meet product standards in quality inspections for defects and foreign bodies, and scraps generated by cutting the sheet. In recent years, efforts toward a sustainable society have been progressing, and it is preferable to effectively reuse the above-mentioned defective products and scraps as rework materials rather than disposing of them.

[0007] However, in general, styrene-based copolymers such as MS resins are not compatible with methacrylic resins, and there is a refractive index difference between these resins, so that a laminate sheet using the above-mentioned rework material as a base layer material may have a decreased transparency and become cloudy. In fact, Patent Document 3 describes that "in order to suppress the occurrence of cloudiness and maintain transparency, the styrene content in the base layer is preferably 1% by mass or less, more preferably 0.85% by mass or less" (paragraph 0171), and the amount of styrene that can be contained in the base layer is very small. In addition, this document does not disclose an example in which a laminate sheet manufactured in the past containing a methacrylic resin and a styrene-based copolymer such as MS resin is used as a rework material. It is preferable to be able to use more rework material as a base layer material.

[0008] The present disclosure has been made in consideration of the above-mentioned problems, and aims to provide a laminate sheet that is suitable for inkjet printing and / or laser cutting processing, etc., and has excellent sustainability. [Means for solving the problem]

[0009] The present disclosure provides the following laminate sheets [1] to

[13] , a manufacturing method thereof, a printed matter, and a molded article. [1] A laminated sheet having a base layer and a surface layer laminated on at least one side of the base layer, The base layer contains a methacrylic resin (M) containing 80 to 100 mass% of methyl methacrylate units, The surface layer is a laminate sheet containing an acrylonitrile-styrene copolymer (AS-E) in which, when gradient high performance liquid chromatography analysis is performed under the following conditions using two eluents, n-hexane and chloroform, the proportion of copolymers having a composition with an elution time of 9 minutes or less is 0 to 5 mass %, the proportion of copolymers having a composition with an elution time of 23 minutes or more is 0 to 5 mass %, and the elution time of the peak top of the maximum peak in the chromatogram is 9 to 23 minutes. <Gradient high performance liquid chromatography analysis conditions> The column used is a silica gel column with an inner diameter of 4.6 mm and a length of 25 cm, packed with spherical fully porous silica gel with a particle size of 5 μm. The column temperature is set to 40° C. A sample solution with a concentration of 0.5 mg / mL is prepared using chloroform as a solvent. When the time from the start of analysis is T (min), the gradient profile of the mobile phase is as follows: The mobile phase between T=0 and T=5 is a mixed solution of n-hexane / chloroform (50 vol% / 50 vol%). Between T=5 and T=20, the chloroform concentration in the mobile phase is increased at a constant rate from 50 vol.% to 100 vol.%. The mobile phase between T=20 and T=25 is 100 vol% chloroform. The flow rate of the mobile phase is 0.8 mL / min. As a detector, an absorbance detector with a detection wavelength of 260 nm is used.

[0010] [2] The maximum peak of the chromatogram of acrylonitrile-styrene copolymer (AS-E) has a peak top elution time of 15 to 22 minutes, and the peak width (W 0.05h ) is 1 to 5 minutes, and the symmetry coefficient (S) measured in accordance with JIS K0124 is 1.2 to 3.4.

[0011] [3] The laminate sheet according to [1] or [2], wherein the average styrene-based monomer unit concentration in the entire laminate sheet is 0.1 to 20 mass %. [4] The laminate sheet according to any one of [1] to [3], wherein the base layer is made of a methacrylic resin composition (MR) containing a methacrylic resin (M) and an acrylonitrile-styrene copolymer (AS-E). [5] The laminate sheet according to any one of [1] to [4], wherein the content of a styrene-based monomer unit in a constituent resin of the base layer is 0 to 10.0% by mass. [6] The laminate sheet according to [5], wherein the content of styrene-based monomer units in the constituent resin of the base layer is 1.2 to 10.0 mass %.

[0012] [7] The laminate sheet of [4], wherein at least a portion of the total raw materials of the base material layer is a recycled resin composition (R) consisting of pulverized material of the laminate sheet produced in the past or a processed product of the pulverized material. [8] The laminate sheet of any of [1] to [7], wherein the laminate sheet has a total thickness of 1 to 10 mm. [9] A laminate sheet according to any one of [1] to [8], which is for inkjet printing and / or laser cutting.

[10] A laminate sheet of any one of [1] to [9], which is a coextrusion molding sheet.

[0013]

[11] A printed matter, obtained by subjecting the surface layer of the laminate sheet according to any one of [1] to

[10] to inkjet printing.

[12] A molded product obtained by applying inkjet printing and laser cutting to any of the laminated sheets [1] to

[10] .

[13] A method for producing a laminate sheet according to [4], comprising co-extrusion molding the laminate sheet using a recycled resin composition (R) consisting of pulverized material of the laminate sheet previously produced or a processed product of the pulverized material, as at least a portion of the total raw material of the base material layer. Effect of the Invention

[0014] According to the present disclosure, it is possible to provide a laminate sheet that is suitable for inkjet printing and / or laser cutting processing, and has excellent sustainability. [Brief description of the drawings]

[0015] [Figure 1] 1 is a schematic cross-sectional view of a laminate sheet according to a first embodiment of the present invention. [Diagram 2] FIG. 4 is a schematic cross-sectional view of a laminate sheet according to a second embodiment of the present invention. [Diagram 3] 1 is a chromatogram obtained by gradient high performance liquid chromatography (gradient HPLC) analysis of the acrylonitrile-styrene copolymer (AS) used in the section [Examples]. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] [Laminated sheet] The laminate sheet of the present disclosure has a base layer and a surface layer laminated on at least one side of the base layer. The base layer contains a methacrylic resin (M) containing 80 to 100 mass% of methyl methacrylate (MMA) units, and the surface layer contains a styrene copolymer (S). The laminate sheet of the present disclosure is suitable for inkjet printing and / or laser cutting.

[0017] The laminated structure of the laminated sheet of the present disclosure may be a two-layer structure having a surface layer on one side of the base layer of the first embodiment shown in FIG. 1. In the figure, reference numeral 16X denotes the laminated sheet, reference numeral 21 denotes the base layer, and reference numeral 31 denotes the surface layer. The laminated sheet of the present disclosure may include any layer other than the base layer and the surface layer as necessary. However, the surface 31S of the surface layer 31 opposite the base layer does not have any other layer thereon and is an exposed surface. This exposed surface may be a printing surface on which printing is performed.

[0018] The laminated structure of the laminated sheet of the present disclosure may be a three-layer structure having surface layers on both sides of the base layer of the second embodiment shown in FIG. 2. In the figure, reference numeral 16Y denotes a laminated sheet, reference numeral 21 denotes a base layer, reference numeral 32 denotes a first surface layer, and reference numeral 33 denotes a second surface layer. The second laminated sheet of the present disclosure may include any other layer other than the base layer and the surface layer, as necessary. However, the surface 32S of the first surface layer 32 opposite the base layer and / or the surface 33S of the second surface layer 33 opposite the base layer have no other layer thereon and are exposed surfaces. This exposed surface may be a printing surface on which printing is applied. In a three-layer laminated sheet, the thickness and composition of the two surface layers may be the same or different.

[0019] The laminated sheet of the present disclosure is suitable as a resin sheet for inkjet printing. Examples of inkjet printing methods include an electrostatic suction method, a method in which a piezoelectric element such as a piezo element is used to apply mechanical vibration or displacement to ink, a method in which ink is heated to foam and the resulting pressure is utilized, and a method in which ultraviolet (UV) curable ink is used. The laminate sheet of the present disclosure can be inkjet printed on the surface layer. The laminate sheet of the present disclosure can also be cut using a laser, an NC router, or the like, as necessary, after inkjet printing, to form into a desired shape. The molded product thus obtained can be preferably used for miscellaneous goods and fixtures such as key holders. In such applications, a UV-curable ink or the like is preferably used as the inkjet printing ink.

[0020] In general, styrene copolymers having an aromatic ring structure in the molecule have good permeability and good adhesion to inkjet printing inks such as UV-curable inks. However, styrene copolymers having an aromatic ring structure do not have good laser cutting processability, and when the resin melts and evaporates due to laser light irradiation, the evaporated gas may cause an unpleasant odor or smoke. In addition, when the melted part cools and solidifies again after the laser cutting process is completed, the evaporated gas may adhere to the cut surface, causing a poor appearance of the cut surface. In general, methacrylic resins suppress the above problems caused by evaporated gas (unpleasant odor or smoke caused by evaporated gas, and poor appearance of the cut surface caused by adhesion of evaporated gas) and have good laser cutting processability. However, they tend to have poor permeability for inkjet printing inks such as UV-curable inks, and poor adhesion for inkjet printing inks.

[0021] The laminate sheet of the present disclosure has a surface layer containing a styrene-based copolymer (S) having an aromatic ring structure in the molecule, and therefore has good permeability to inkjet printing inks such as UV-curable inks and good adhesion to inkjet printing inks. The laminate sheet of the present disclosure has a laminated structure of a base layer containing a methacrylic resin (M) and a surface layer containing a styrene copolymer (S), and the proportion of styrene monomer units in the entire laminate sheet is reduced, thereby suppressing the above-mentioned problems caused by evaporated gas during laser cutting (unpleasant odor or smoke caused by evaporated gas, and poor appearance of the cut surface caused by adhesion of evaporated gas) and improving laser cutting processability.

[0022] In the laminate sheet of the present disclosure, the ratio of the total thickness of the surface layer to the total thickness of the laminate sheet is not particularly limited, and is preferably 1 to 20%. The lower limit is more preferably 2%, and particularly preferably 3%. The upper limit is more preferably 15%, and particularly preferably 10%. When the ratio of the total thickness of the surface layer is equal to or greater than the above lower limit, the thickness of the surface layer containing the styrene copolymer (S) is sufficiently ensured, and good ink adhesion can be ensured. When the ratio of the total thickness of the surface layer is equal to or less than the above upper limit, the content of the styrene monomer unit in the laminate sheet can be reduced, and unpleasant odors or smoke due to evaporated gas during laser cutting and poor appearance of the cut surface due to adhesion of evaporated gas can be suppressed.

[0023] In this specification, the "average styrene monomer unit concentration in the entire laminate sheet" refers to the ratio of the total mass of the styrene monomer units in the laminate sheet to the total mass of the laminate sheet. This average styrene monomer unit concentration is not particularly limited, and is preferably 0.1 to 20 mass%. The lower limit is more preferably 0.5 mass%, particularly preferably 1.0 mass%, and most preferably 2.0 mass%. The upper limit is more preferably 15 mass%, particularly preferably 10 mass%. When the average styrene monomer unit concentration in the entire laminate sheet is equal to or higher than the lower limit, good ink adhesion can be ensured, and when it is equal to or lower than the upper limit, odor or smoke due to evaporated gas during laser cutting and poor appearance of the cut surface due to adhesion of evaporated gas can be suppressed.

[0024] The laminated sheets of the present disclosure are preferably coextruded sheets. In the laminate sheet of the present disclosure, the total thickness of the laminate sheet is not particularly limited, and is preferably 1 to 10 mm, more preferably 1 to 5 mm, in order to improve inkjet printability and laser cutting processability. For example, when the total thickness of the laminate sheet is 3 mm, the thickness of the base layer is preferably 2.4 to 2.9 mm, the thickness of one surface layer is preferably 30 to 300 μm, and the total thickness of the surface layers is preferably 30 to 600 μm.

[0025] The haze value of the 3.0 mm thick monolayer molded sheet of the pulverized laminate sheet of the present disclosure is not particularly limited, and is preferably 4% or less, more preferably 3% or less, particularly preferably 2% or less, and most preferably 1% or less. The haze value of the monolayer molded sheet can be realized by using a specific styrene copolymer having good compatibility with the methacrylic resin (M) as the styrene copolymer (S) contained in the surface layer. If the haze value of the monolayer molded sheet is 4% or less, the laminate sheet of the present disclosure having excellent transparency can be manufactured using a pulverized laminate sheet of the present disclosure manufactured in the past or a recycled resin composition (R) made of the pulverized laminate sheet as at least a part of the total raw material of the base layer. The laminate sheet of the present disclosure having the above characteristics can be used as a rework material or can contain a rework material, and has excellent sustainability. In this specification, unless otherwise specified, "transparent" is defined as a haze value of 4% or less.

[0026] A 3.0 mm thick single-layer molded sheet of the pulverized laminate sheet of the present disclosure can be obtained by a known method, for example, as follows. The laminated sheet of the present disclosure is pulverized using a known resin pulverizer. The pulverized material obtained is melt-kneaded using an extruder and a kneading / extrusion tester ("Labo Plastomill (registered trademark)" manufactured by Toyo Seiki Seisakusho) to obtain a uniform resin composition. The molten kneaded material obtained is molded by a known method such as hot press molding to obtain a single-layer molded sheet having a thickness of 3.0 mm. The melt-kneading temperature and molding temperature in the molding of the single-layer molded sheet are preferably within the range of the suitable melt-kneading temperature of the base layer material when molding (preferably co-extrusion molding) the laminated sheet of the present disclosure, and may be, for example, the maximum temperature in the extruder used for melt-kneading the base layer material when molding (preferably co-extrusion molding) the laminated sheet of the present disclosure. The melt-kneading temperature and molding temperature in the molding of the single-layer molded sheet are preferably 190 to 280°C, more preferably 210 to 270°C, particularly preferably 230 to 260°C, and for example, 250°C is preferred.

[0027] The haze value of the laminate sheet of the present disclosure is not particularly limited, and is preferably 4% or less, more preferably 3% or less, particularly preferably 2% or less, and most preferably 1% or less. By using a specific styrene copolymer having good compatibility with the methacrylic resin (M) as the styrene copolymer (S) contained in the surface layer, even if a recycled resin composition (R) consisting of a crushed product of the laminate sheet of the present disclosure produced in the past or a processed product of the crushed product is used as at least a part of the entire raw material of the base layer, the laminate sheet of the present disclosure having a low haze value and excellent transparency can be produced.

[0028] (Surface layer) The surface layer contains one or more styrene copolymers (S). Examples of the styrene monomer units contained in the styrene copolymers (S) include styrene, α-methylstyrene, o-, m- or p-methylstyrene, and combinations thereof, with styrene (St) being preferred. In the laminate sheet of the present disclosure, the one or more styrene-based copolymers (S) include an acrylonitrile-styrene-based copolymer (AS) that has good compatibility with the methacrylic resin (M). From the viewpoint of compatibility with the methacrylic resin (M), the content of styrene units in the acrylonitrile-styrene copolymer (AS) is preferably 70 to 95% by mass. The lower limit is more preferably 73% by mass, and particularly preferably 76% by mass. The upper limit is more preferably 90% by mass, and particularly preferably 88% by mass.

[0029] In the laminate sheet of the present disclosure, the surface layer contains an acrylonitrile-styrene copolymer (AS-E) having specific properties due to its good compatibility with the methacrylic resin (M) among acrylonitrile-styrene copolymers (AS). When an acrylonitrile-styrene copolymer (AS-E) is subjected to gradient high performance liquid chromatography (gradient HPLC) analysis under the following conditions using two eluents, n-hexane and chloroform, the ratio of copolymers having a composition with an elution time of 9 minutes or less is 0 to 5 mass%, the ratio of copolymers having a composition with an elution time of 23 minutes or more is 0 to 5 mass%, and the elution time of the maximum peak top of the chromatogram is 9 to 23 minutes.

[0030] <Gradient high performance liquid chromatography (gradient HPLC) analysis conditions> The column used is a silica gel column with an inner diameter of 4.6 mm and a length of 25 cm, packed with spherical fully porous silica gel with a particle size of 5 μm. The column temperature is set to 40° C. A sample solution with a concentration of 0.5 mg / mL is prepared using chloroform as a solvent. When the time from the start of analysis is T (min), the gradient profile of the mobile phase is as follows: The mobile phase between T=0 and T=5 is a mixed solution of n-hexane / chloroform (50 vol% / 50 vol%). Between T=5 and T=20, the chloroform concentration in the mobile phase is increased at a constant rate from 50 vol% to 100 vol%. The mobile phase between T=20 and T=25 is 100 vol% chloroform. The flow rate of the mobile phase is 0.8 mL / min. As a detector, an absorbance detector with a detection wavelength of 260 nm is used.

[0031] According to the research of the present inventors, it was found that in the above-mentioned gradient HPLC analysis, both the copolymers eluted very early with an elution time of 9 minutes or less and the copolymers eluted very late with an elution time of 23 minutes or more have poor compatibility with the methacrylic resin (M). In the above-mentioned gradient HPLC analysis, the ratio of the copolymers eluted very early with an elution time of 9 minutes or less is below the above-mentioned upper limit value, the ratio of the copolymers eluted very late with an elution time of 23 minutes or more is below the above-mentioned upper limit value, and the elution time of the peak top of the maximum peak in the chromatogram is 9 to 23 minutes, and is therefore excellent in compatibility with the methacrylic resin (M), and is preferable.

[0032] From the viewpoint of compatibility with the methacrylic resin (M), the upper limit of the proportion of the copolymer having a composition having an elution time of 9 minutes or less in the above-mentioned gradient HPLC analysis is preferably 4% by mass, more preferably 3% by mass, particularly preferably 2% by mass, and most preferably 1% by mass. From the viewpoint of compatibility with the methacrylic resin (M), the upper limit of the proportion of the copolymer having a composition with an elution time of 23 minutes or longer in the above-mentioned gradient HPLC analysis is preferably 4% by mass, more preferably 3% by mass.

[0033] From the viewpoint of compatibility with the methacrylic resin (M), the lower limit of the elution time of the peak top of the maximum peak in the chromatogram obtained in the gradient HPLC analysis is more preferably 10 minutes, particularly preferably 12 minutes, and most preferably 15 minutes. From the viewpoint of compatibility with the methacrylic resin (M), the upper limit of the elution time of the peak top of the maximum peak in the chromatogram obtained in the gradient HPLC analysis is more preferably 22 minutes, particularly preferably 21 minutes, and most preferably 20 minutes.

[0034] From the viewpoint of compatibility with the methacrylic resin (M) and transparency of the base layer, the maximum peak of the chromatogram obtained in the gradient HPLC analysis is determined to be a peak width (W 0.05h) is 1 to 5 minutes, and the symmetry coefficient (S) measured in accordance with JIS K0124 is preferably 1.2 to 3.4. Peak width at 5% height (W 0.05h The lower limit of the above is more preferably 2 minutes, particularly preferably 3 minutes, and most preferably 4 minutes. The lower limit of the symmetry coefficient (S) is more preferably 1.3, particularly preferably 1.4, and most preferably 1.5. The upper limit of the symmetry coefficient (S) is more preferably 3.2, even more preferably 3.0, even more preferably 2.8, particularly preferably 2.5, and most preferably 2.0. For specific examples of gradient HPLC analysis and measurement of various parameters, see the Examples section below.

[0035] The surface layer may contain one or more acrylonitrile-styrene copolymers (AS) other than the acrylonitrile-styrene copolymers (AS-E) having the above-mentioned specific properties. The content of the acrylonitrile-styrene copolymer (AS-E) in the surface layer is preferably 90 to 100% by mass. The lower limit is more preferably 95% by mass, and particularly preferably 98% by mass.

[0036] Commercially available acrylonitrile-styrene copolymers (AS) include "LiTac-A100PCF" and "120PCF" manufactured by Nippon A&L Co., Ltd.; "Sunrex SAN-C", "SAN-R", and "SAN-H" manufactured by Techno UMG; "Denka ASAS-C-800" and "AS-C-820" manufactured by Denka Co., Ltd.; "Toyolac" manufactured by Toray Industries, Inc.; and "Cevian N" manufactured by Daicel Miraize Co., Ltd. The acrylonitrile-styrene copolymer (AS-E) can be selected from the above-mentioned commercially available products having the above-mentioned specific properties, and examples thereof include "LiTac-A 100PCF" manufactured by Nippon A&L Co., Ltd.; "Sunrex SAN-C" manufactured by Techno UMG Co., Ltd.; and "Denka AS AS-C-820" manufactured by Denka Co., Ltd.

[0037] Within the range that satisfies the characteristic that the haze value of a 3.0 mm thick single-layer molded sheet of the pulverized laminate sheet of the present disclosure is 4% or less, the surface layer may contain, in addition to the acrylonitrile-styrene copolymer (AS), one or more other styrene copolymers (S) that are compatible with the methacrylic resin (M), as necessary. Other styrene copolymers (S) compatible with the methacrylic resin (M) include styrene-maleic anhydride copolymer (SMA) and methyl methacrylate-styrene copolymer (MS), etc. Among them, from the viewpoint of compatibility with the methacrylic resin (M), styrene-maleic anhydride copolymer (SMA) etc. are preferred.

[0038] From the viewpoint of compatibility with the methacrylic resin (M), the styrene unit concentration in the styrene-maleic anhydride copolymer (SMA) is preferably 60 to 95% by mass. The lower limit is more preferably 65% ​​by mass, particularly preferably 70% by mass, and most preferably 75% by mass. The upper limit is more preferably 90% by mass, particularly preferably 85% by mass, and most preferably 80% by mass. Commercially available styrene-maleic anhydride copolymers (SMA) include "XIRAN" and "XIBOND" manufactured by Polyscope; "SMA-700" manufactured by Jiaxing Huawen Chemical; and "SAM-020" manufactured by Fine-blend Polymer.

[0039] A small amount of methyl methacrylate-styrene copolymer (MS) is compatible with the methacrylic resin (M) and can be used. The amount of the methyl methacrylate-styrene copolymer (MS) in the surface layer is preferably 0 to 1.5 mass%, more preferably 0 to 1.2 mass%, particularly preferably 0 to 1.0 mass%, and most preferably 0 to 0.85 mass%. From the viewpoint of compatibility with the methacrylic resin (M), the styrene unit concentration in the methyl methacrylate-styrene copolymer (MS) is preferably 35 to 50 mass%. The upper limit is more preferably 45 mass%. Commercially available products of methyl methacrylate-styrene copolymers (MS) include "TOYO MS MS600" manufactured by Toyo Styrene Co., Ltd.; "DENKA TX Polymer TX-100S" manufactured by Denka Co., Ltd.; and "Cevian NAS" manufactured by Daicel Miraize Co., Ltd.

[0040] Acrylonitrile-butadiene-styrene copolymer (ABS), methyl methacrylate-butadiene-styrene copolymer (MBS), and high impact polystyrene grafted with butadiene (HIPS) are preferably not used as the styrene copolymer (S) because they are poorly compatible with the methacrylic resin (M).

[0041] Within the range where the haze value of a 3.0 mm-thick single-layer molded sheet of the pulverized laminate sheet of the present disclosure is 4% or less, the surface layer may contain one or more methacrylic resins (M) and / or one or more other acrylic resins (A) other than the methacrylic resin (M) as necessary. Examples of the optional other acrylic resins (A) are the same as those of the base layer. The methacrylic resin (M) in the surface layer may be the same or different from the methacrylic resin (M) in the base layer. The same applies to the optional other acrylic resins (A). The content of the methacrylic resin (M) and / or other acrylic resin (A) in the surface layer (total amount in the case of a plurality of types unless otherwise specified) is preferably 0 to 10% by mass. The upper limit is more preferably 5% by mass, particularly preferably 2% by mass.

[0042] Within the range where the haze value of a 3.0 mm-thick single-layer molded sheet of the pulverized laminate sheet of the present disclosure is 4% or less, the surface layer may contain one or more other polymers other than the styrene polymer (S), the methacrylic resin (M), and the other acrylic resin (A) as necessary. The other polymers are not particularly limited, and include other thermoplastic resins such as polyolefins such as polyethylene and polypropylene, polyamide, polyphenylene sulfide, polyether ether ketone, polyester, polysulfone, polyphenylene oxide, polyimide, polyetherimide, and polyacetal; and thermosetting resins such as phenolic resins, melamine resins, silicone resins, and epoxy resins. The content of the other polymers in the surface layer (total amount in the case of multiple types unless otherwise specified) is preferably 0 to 10% by mass. The upper limit is more preferably 5% by mass, and particularly preferably 2% by mass.

[0043] The surface layer may contain various additives as necessary within the range where the haze value of a 3.0 mm thick single-layer molded sheet of the pulverized laminate sheet of the present disclosure is 4% or less. Examples of additives include colorants, antioxidants, heat deterioration inhibitors, UV absorbers, light stabilizers, lubricants, release agents, polymer processing aids, antistatic agents, flame retardants, light diffusing agents, matting agents, rubber components (impact resistance modifiers) such as core-shell particles and block copolymers, and fluorescent materials. The content of the additives can be appropriately set within a range that does not impair the effects of the present invention. For example, the content of the antioxidant is preferably 0.01 to 1 part by mass, the content of the ultraviolet absorber is preferably 0.01 to 3 parts by mass, the content of the light stabilizer is preferably 0.01 to 3 parts by mass, and the content of the lubricant is preferably 0.01 to 3 parts by mass, relative to 100 parts by mass of the constituent resin of the surface layer (100 parts by mass in total when multiple types are used). When other polymers and / or additives are added to the surface layer, the timing of addition may be during or after polymerization of the styrene-based copolymer (S).

[0044] The glass transition temperature (Tg) of the constituent resin of the surface layer (a mixed resin composition when multiple types are used) is not particularly limited, and is preferably 80 to 160°C, more preferably 100 to 110°C.

[0045] (base material layer) The substrate layer contains one or more methacrylic resins (M). The methacrylic resin (M) is a homopolymer or copolymer containing methyl methacrylate (MMA) units. From the viewpoint of transparency, the content of MMA units in the methacrylic resin (M) is 80 to 100% by mass. The lower limit is preferably 90% by mass, more preferably 95% by mass.

[0046] The methacrylic resin (M) may contain one or more (meth)acrylic acid ester units other than MMA units. Examples of (meth)acrylic acid esters other than MMA include methyl acrylate (MA), ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, stearyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and the like. Examples of the acrylates include acrylate, 4-hydroxybutyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, trifluoromethyl (meth)acrylate, trifluoroethyl (meth)acrylate, pentafluoroethyl (meth)acrylate, glycidyl (meth)acrylate, allyl (meth)acrylate, phenyl (meth)acrylate, toluyl (meth)acrylate, benzyl (meth)acrylate, isobornyl (meth)acrylate, and 3-dimethylaminoethyl (meth)acrylate. Among these, MA is preferred from the viewpoint of transparency. For example, a copolymer of MMA and MA is preferred because it has excellent transparency. In this specification, (meth)acrylic is a general term for acrylic and methacrylic, and the same applies to (meth)acrylic acid, (meth)acrylonitrile, and the like.

[0047] The substrate layer may contain one or more other acrylic resins (A) other than the methacrylic resin (M) as necessary. In this specification, the "other acrylic resin (A)" refers to a methacrylic resin having an MMA unit content of less than 80 mass% and / or a (meth)acrylic resin that does not contain MMA units and contains one or more (meth)acrylic acid ester units other than MMA units.

[0048] The methacrylic resin (M) and the other acrylic resin (A) may contain structural units derived from one or more other monomers other than (meth)acrylic acid esters. Examples of the other monomers include (meth)acrylic acid, (meth)acrylic acid metal salts, (meth)acrylonitrile, (meth)acrylamide, vinyl monomers such as vinyl chloride and vinyl acetate, acid anhydrides such as maleic anhydride, maleimides such as phenylmaleimide and cyclohexylmaleimide, and styrene monomers such as styrene, α-methylstyrene, and vinyltoluene. The content (total amount when multiple types are present) of structural units derived from monomers other than (meth)acrylic acid esters in the methacrylic resin (M) and the other acrylic resin (A) is preferably 0 to 10 mass%, more preferably 5 mass%, particularly preferably 2 mass%. The content of styrene monomer units in the methacrylic resin (M) and the other acrylic resin (A) (when multiple types are present, the total amount) is preferably 0 to 1.5 mass%, and the upper limit is more preferably 1.2 mass%, particularly preferably 1.0 mass%, and most preferably 0.85 mass%.

[0049] The methacrylic resin (M) and the other acrylic resin (A) are obtained by polymerizing one or more (meth)acrylic acid esters and, if necessary, other monomers. When using multiple types of monomers, the multiple types of monomers are usually mixed to prepare a monomer mixture, and then polymerization is performed. There are no particular limitations on the polymerization method, and from the viewpoint of productivity, radical polymerization methods such as bulk polymerization, suspension polymerization, solution polymerization, and emulsion polymerization are preferred.

[0050] Within the range where the haze value of a 3.0 mm thick monolayer molded sheet of the pulverized laminate sheet of the present disclosure is 4% or less, the substrate layer may contain one or more styrene copolymers (S) as necessary. The styrene copolymer (S) in the substrate layer may be the same or different from the styrene copolymer (S) in the surface layer. The substrate layer may be made of a methacrylic resin composition (MR) containing a methacrylic resin (M) and an acrylonitrile-styrene copolymer (AS-E). When the base layer contains a styrene-based monomer unit, there is a tendency that the amount of change in warpage of the laminate sheet after being left standing in a high-humidity environment can be effectively reduced.

[0051] In general, in the production of (co)extrusion molded sheets and molded products using the same, there are defective products that arise when the extrusion molding production line is started up, scraps generated by trimming both ends of the sheet, defective products that are determined not to meet product standards in quality inspections for defects and foreign bodies, and scraps generated by cutting the sheet. In recent years, efforts toward a sustainable society have been progressing, and it is preferable to effectively reuse the above-mentioned defective products and scraps as rework materials rather than disposing of them. In this specification, a "virgin material" is a molding material that has never been subjected to molding processing in the past, and a "rework material" is a molding material that has been molded into a molded product at least once in the past. At least a part of the total raw material of the base layer can be a recycled resin composition (R) (also called a rework material) consisting of a crushed product of the laminate sheet of the present disclosure that was previously manufactured or a processed product of the crushed product. The form of the processed product can be a strand, a pellet, or the like. As described above, the haze value of a 3.0 mm thick single-layer molded sheet of the pulverized laminate sheet of the present disclosure is 4% or less. Therefore, a laminate sheet of the present disclosure having excellent transparency can be manufactured using a recycled resin composition (R) consisting of pulverized material of a laminate sheet of the present disclosure produced in the past or a processed product of the pulverized material as at least a part of the total raw material of the base layer.

[0052] The content of styrene-based monomer units in the constituent resin of the base layer is not particularly limited, and is preferably 0 to 10.0% by mass. Patent Document 3, listed in the [Background Art] section, states that "in order to suppress the occurrence of cloudiness and maintain transparency, the styrene content in the constituent resin of the base layer is preferably 1 mass % or less, and more preferably 0.85 mass % or less" (paragraph 0171). In the technology of the present disclosure, the content of the styrene-based monomer unit in the constituent resin of the base layer can be made larger than the range described in Patent Document 3, and can be made 1.2 mass% or more, 1.5 mass% or more, 2.0 mass% or more, 2.5 mass% or more, 3.0 mass% or more, 3.5 mass% or more, or 4.0 mass% or more. The upper limit is more preferably 9.0 mass%, particularly preferably 8.5 mass%, and most preferably 8.0 mass%.

[0053] Within the range where the haze value of a 3.0 mm thick single-layer molded sheet of the pulverized laminate sheet of the present disclosure is 4% or less, the base layer may contain one or more other polymers other than the methacrylic resin (M), other acrylic resin (A), and styrene polymer (S) as required. The base layer may contain various additives as required. Examples of the types of other polymers and additives and the preferred amounts of addition are the same as those of the surface layer.

[0054] The glass transition temperature (Tg) of the constituent resin of the base layer (a mixed resin composition when multiple resins are used) is not particularly limited, and is preferably 100 to 140°C, more preferably 105 to 135°C, and particularly preferably 105 to 125°C.

[0055] [Manufacturing method of laminated sheet] The laminated sheet of the present disclosure can be manufactured by a known sheet molding method, and from the viewpoints of production efficiency and interlayer adhesion, an extrusion molding method, etc. is preferred. In the case of the extrusion molding method, a co-extrusion molding is preferred in which a base layer material containing one or more methacrylic resins (M) and a surface layer material containing one or more styrene copolymers (S) including an acrylonitrile-styrene copolymer (AS-E) melt-kneaded using different extruders are co-extruded from a common extrusion die (such as a T-die).

[0056] Co-extrusion die types include a multi-manifold die type and a field block type. In the feed block type, a molten base material layer material containing a methacrylic resin (M) and a molten surface layer material containing a styrene copolymer (S) are laminated in a feed block, then guided to a T-die or the like to be formed into a sheet and co-extruded. In the multi-manifold die type, a molten base material layer material containing a methacrylic resin (M) and a molten surface layer material containing a styrene copolymer (S) are guided to a T-die or the like to be formed into a sheet, then guided to a T-die or the like to be formed into a sheet, then laminated and co-extruded. In the laminate sheet of the present disclosure, the surface layer is designed to be thin. In this case, the multi-manifold die type is preferred. In either method, the thermoplastic resin laminate extruded from a T-die or the like is cooled by passing through a gap between at least a pair of cooling pressure rolls, and then taken up by a take-up roll. The above co-extrusion, cooling, and take-up steps are carried out continuously. In this specification, the heated and molten state is mainly referred to as a "thermoplastic resin laminate" and the solidified state is referred to as a "laminate sheet", but there is no clear boundary between the two.

[0057] In the co-extrusion molding of the laminated sheet of the present disclosure, the T die temperature (Td) is preferably 190 to 280°C. If Td is less than 190°C, the melt viscosity of the methacrylic resin (M) and the styrene copolymer (S) may become too high, and these resins may not be extruded satisfactorily. If Td is more than 280°C, the styrene copolymer (S) may decompose due to high temperature. Td is more preferably 210 to 270°C, particularly preferably 230 to 260°C. The lip thickness of the T-die is designed according to the desired total thickness of the laminate sheet (preferably 1 to 10 mm). The take-up speed (V) of the laminated sheet by the pair of take-up rolls is not particularly limited, and is preferably 0.5 to 2.0 m / min.

[0058] In the manufacturing method of the laminate sheet of the present disclosure, the laminate sheet of the present disclosure can be co-extrusion molded using a recycled resin composition (R) consisting of pulverized material of a laminate sheet of the present disclosure previously manufactured or a processed product of the pulverized material, as at least a portion of the total raw material of the base layer. The proportion of the recycled resin composition (R) in the total raw materials of the base layer is not particularly limited and can be, for example, 1 to 100% by mass. In the technology of the present disclosure, the proportion of the recycled resin composition (R) in the total raw materials of the base layer can be increased, and can be 10 to 100% by mass, 20 to 100% by mass, 30 to 100% by mass, 40 to 100% by mass, or 50 to 100% by mass.

[0059] Generally, when the same material is repeatedly reworked, the quality of the rework material may deteriorate, and the haze value of the laminated sheet using the rework material may increase. Taking into consideration the number of reworks or the quality of the rework material, it is preferable to adjust the proportion of the rework material used within a range that satisfies the characteristic that the haze value of a 3.0 mm-thick laminated sheet using the crushed laminated sheet of the present disclosure as the base layer is 4% or less. Even when at least a portion of the total raw materials of the base layer is a recycled resin composition (R) consisting of pulverized material of a laminate sheet of the present disclosure that was previously manufactured or a processed product of the pulverized material, the laminate sheet of the present disclosure has excellent transparency and can have a haze value at a thickness of 3.0 mm of 4% or less, 3% or less, 2% or less, or 1% or less.

[0060] [Printed materials, molded products] The laminate sheet of the present disclosure can be preferably used as a resin sheet for inkjet printing. A printed matter can be provided by performing inkjet printing on the surface layer containing the styrene copolymer (S) contained in the laminate sheet of the present disclosure. The laminate sheet of the present disclosure can also be cut using a laser and an NC router, etc., as necessary, after the inkjet printing, to form it into a desired shape. The laminated sheet of the present disclosure has good laser cutting processability, so that fine cutting can be performed. For example, a molded product having a curved cut portion with a radius of 0.5 to 2 mm can be manufactured with good shape accuracy. The laminated sheet of the present disclosure has good laser cutting processability, so that a high-power laser processing machine can be used to perform cutting at high speed with good productivity. For example, the laminated sheet of the present disclosure can be cut at a speed of 350 cm / min or more with a laser processing machine with an output of 100 W or more to manufacture a molded product.

[0061] As described above, according to the present disclosure, it is possible to provide a laminate sheet that is suitable for use in inkjet printing and / or laser cutting processing, and has excellent sustainability.

[0062] [Application] The laminated sheets, printed matter, and molded articles of the present disclosure can be used in a variety of fields, such as printing, advertising, sign and display, events, amusement, architecture, and interior design. The laminated sheet, printed matter, and molded article of the present disclosure can be preferably used for miscellaneous goods and fixtures such as key holders, figurines, and character panels. EXAMPLES

[0063] Examples and comparative examples according to the present invention will be described below. [Evaluation items and evaluation methods] (Content of styrene units in acrylonitrile-styrene copolymer (AS)) Using a nuclear magnetic resonance spectrometer (Bruker's "ULTRA SHIELD 400 PLUS"), the acrylonitrile-styrene copolymer (AS) 1 H-NMR spectrum was measured. The styrene unit concentration was calculated from the integral value of the peaks derived from the hydrogen atoms bonded to the carbon atoms at positions 2 to 6 of the aromatic ring contained in styrene.

[0064] (Gradient High Performance Liquid Chromatography (Gradient HPLC) Analysis) Gradient high performance liquid chromatography (gradient HPLC) analysis of acrylonitrile-styrene copolymer (AS) was carried out. The analytical device used was a high-performance liquid chromatograph (HPLC system "Prominence LC-20AD") manufactured by Shimadzu Corporation. The column used was a silica gel column (inner diameter 4.6 mmφ, length 25 cm) filled with spherical fully porous silica gel with a particle size of 5 μm. The column temperature was set to 40°C. A sample solution with a concentration of 0.5 mg / mL was prepared using chloroform as a solvent, and the amount of the sample solution injected into the device was 2 μL. The components in the sample solution were separated by gradient elution using two liquids, n-hexane and chloroform, as the eluents. The high-pressure mixing method was used to mix the two liquids under pressure. The gradient profile of the mobile phase was as follows, where T (minutes) is the time from the start of the analysis (the time when the sample solution was injected into the device). The mobile phase between T=0 and T=5 was a mixed solution of n-hexane / chloroform (50 vol% / 50 vol%, volume ratio 1 / 1). Between T = 5 and T = 20, the chloroform concentration in the mobile phase was increased at a constant rate (50 vol% / 15 min) from 50 vol% to 100 vol% (= the n-hexane in the mobile phase was decreased at a constant rate (50 vol% / 15 min) from 50 vol% to 0 vol%). The mobile phase between T=20 and T=25 was 100 vol% chloroform (also called pure chloroform). Between T = 25 and T = 30, the n-hexane concentration in the mobile phase was increased from 0 vol% to 100 vol% at a constant rate (100 vol% / 5 min) (= the chloroform concentration in the mobile phase was decreased from 100 vol% to 0 vol% at a constant rate (100 vol% / 5 min)). The mobile phase between T=30 and T=60 was a mixed solution of n-hexane / chloroform (50 vol% / 50 vol%, volume ratio 1 / 1). The flow rate of the mobile phase was 0.8 mL / min. As a detector, an absorbance detector (also called a UV detector) with a detection wavelength of 260 nm or an evaporative light scattering (ELS) detector ("ELSD-LTII" manufactured by System Instruments) was used.

[0065] Gradient high performance liquid chromatography (gradient HPLC) analysis was performed under the same conditions as when using the sample solution, using 100 vol% chloroform as a blank sample. Based on the baseline gradient of the measurement data of this blank sample, baseline correction processing was performed on the measurement data of the sample solution to obtain a chromatogram of the sample solution.

[0066] The elution time of a certain component is the time from the start of the analysis (the time when the sample solution is injected into the device) to the detection of the certain component (the time to the top of the peak derived from the certain component), and is also called the retention time. In the obtained chromatogram, the integral values ​​of the peaks with elution times of 9 minutes or less, the integral values ​​of the peaks with elution times of 23 minutes or more, and the integral values ​​of the peaks with elution times of 9 to 23 minutes were calculated, and from these data, the proportion of copolymers having a composition with an elution time of 9 minutes or less and the proportion of copolymers having a composition with an elution time of 23 minutes or more were calculated.

[0067] The elution time of the peak top of the maximum peak (also simply referred to as the elution time of the peak top) and the height (h) of the peak top of the maximum peak from the baseline (also referred to as the peak height (h)) were determined. In addition, the symmetry factor (S) of the maximum peak was determined in accordance with JIS K0124. The symmetry coefficient (S) is a parameter expressed by the following formula. S=(W 0.05h ) / (2f) In the above formula, W 0.05h is the peak width at a height position that is 5% (1 / 20) of the peak height (h) from the baseline (also called the peak width at 5% height). f is this peak width (W 0.05h) is bisected by a line passing through the peak top and perpendicular to the horizontal axis of the chromatogram, and the symmetry factor (S) is the width of the rising side of the peak. The symmetry factor (S) is an index of the symmetry of a peak. The peak height (h) and peak width at 5% height (W 0.05h ), and the relationship between the parameter (f), please refer to FIG. 1 of JP2016-020435A.

[0068] (Haze value of laminated sheet) A 50 mm x 50 mm test piece was cut out from the center of the width direction of a 3.0 mm thick laminated sheet, and the haze value was measured using "HM-150" manufactured by Murakami Color Research Laboratory.

[0069] (Ink adhesion) Inkjet printing was carried out on one surface of the laminate sheet obtained in each example under the following conditions: The printing pattern was a solid print of a roughly ellipse measuring 1.8 cm in minor axis and 2.8 cm in major axis. Equipment: Roland DG "LEF-300" Temperature: room temperature (20~25℃), UV-curable ink (white): Roland DG EUV-BK, UV curable ink (black): Roland DG EUV-WH.

[0070] The ink adhesion was evaluated for the inkjet-printed laminated sheet. In the printed layer consisting of the cured product of white and black UV-curable ink, a 10 mm square evaluation area was cross-cut into 100 squares (10 squares vertically x 10 squares horizontally) at 1 mm intervals vertically and horizontally. Cellophane tape was applied to the entire evaluation area, and the tape was rubbed with an eraser to ensure that the tape was sufficiently adhered to the printed surface, after which the tape was peeled off at a 90° angle. Observation was performed with a 10x magnifying glass, and the number of squares where the ink had peeled off from the laminated sheet was counted out of the 100 squares to be evaluated. The evaluation criteria are as follows: A (Excellent): No ink peeling was observed in any of the squares. B (Good): Ink peeling was observed in squares with 1 or more and less than 10. C (Acceptable): Ink peeling was observed in 10 or more but less than 50 squares. D (Fail): Ink peeling was observed in 50 or more squares.

[0071] (Laser cutting processability) The laminated sheet after inkjet printing was subjected to laser cutting under the following conditions to obtain a molded product in the shape of a TV anime character with dimensions of 20 mm short diameter x 30 mm long diameter and a curved cut part with a radius of 1 mm. Equipment: SEI "MERCURY609" Temperature: room temperature (20~30℃), Laser type: Carbon dioxide laser, Laser power: 200W, Cutting speed: 350~400cm / min. The following evaluations were carried out.

[0072] <Appearance of cutting surface> The 10 molded products obtained after the laser cutting process were evaluated for defects on the cutting surface of the 30 cm straight cut section by optical microscope observation and finger touch inspection. The main defects are as follows: Roughness: The cutting surface was not uniform overall and felt rough to the touch. Rough corners: The corners of the cut surface were partially rough and felt rough to the touch. Resin pool: Molten resin pool was observed on some parts of the cutting surface. Foreign matter: Colored foreign matter was found on the cutting surface. The evaluation criteria are as follows: A (Excellent): The number of molded products with defects is 0 to 1. B (Good): The number of molded products with defects is 2 to 4. C (Fail): The number of molded products with defects is 5 to 10.

[0073] <Whether or not smoke or odor is generated> The presence or absence of smoke or odor generation during laser cutting was evaluated sensorily. The evaluation criteria are as follows: A (Good): There was some smoke or odor, but it was not noticeable. B(Acceptable): Between A and C. C (bad): There was noticeable smoke or odor.

[0074] [material] The materials used are as follows: (Methacrylic resin (M)) <pmma1>Methyl methacrylate-methyl acrylate copolymer, "Parapet" manufactured by Kuraray, methyl methacrylate unit content: 94 mass%, methyl acrylate unit content: 6 mass%, styrene unit content: 0 mass%.

[0075] (Acrylonitrile-styrene copolymer (AS)) <as1>Nippon A&L "Lytac-A 100PCF", styrene unit content: 77% by mass, <as2>Techno UMG's "Sunrex SAN-C", styrene unit content: 76% by mass, <as3>Denka AS AS-C-820, styrene unit content: 82% by mass, <asc4>"Cevian-N 020SF" manufactured by Daicel Miraize Co., Ltd., styrene unit content: 74% by mass.

[0076] FIG. 4 shows chromatograms of acrylonitrile-styrene copolymers (AS1) to (AS3) and (ASC4) after baseline correction processing when a UV detector with a detection wavelength of 260 nm was used as the detector in gradient high performance liquid chromatography (gradient HPLC) analysis.

[0077] [Laminated sheet manufacturing] (Examples (EV1-1) to (EV3-1), Comparative Example (ECV11-1)) For the base layer material, virgin methacrylic resin (M) was melted using a 150 mmφ single screw extruder manufactured by Toshiba Machine Co., Ltd. (maximum temperature of the cylinder part: 240°C). For the surface layer material, virgin acrylonitrile-styrene copolymer (AS) was melted using a 65 mmφ single screw extruder manufactured by Toshiba Machine Co., Ltd. (maximum temperature of the cylinder part: 240°C). Using a multi-manifold die, molten acrylonitrile-styrene copolymer (AS), molten methacrylic resin (M), and molten acrylonitrile-styrene copolymer (AS) were layered in this order, extruded from a T-die, cooled using four adjacent cooling rolls, and taken up by a take-up roll. The above co-extrusion By molding, two types of three-layer laminated sheets (LV1-1) to (LV3-1) and (LCV11-1) of acrylonitrile-styrene copolymer (AS) (first surface layer, 0.05 mm thick) / methacrylic resin (M) (base layer, 2.9 mm thick) / acrylonitrile-styrene copolymer (AS) (second surface layer, 0.05 mm thick) were produced. The first surface layer and the second surface layer had the same composition and thickness. The main production conditions and various parameter values ​​are shown in Tables 1 and 2. In Tables 1 to 4, conditions not listed in the tables were common conditions.

[0078] (Example (EV1-2), Comparative Example (ECV11-2)) Except for changing the thickness of the first and second surface layers to 0.15 mm and the thickness of the base layer to 2.7 mm, laminate sheets (LV1-2) and (LCV11-2) were obtained in the same manner as in Example (EV1-1) or Comparative Example (ECV11-1). The main manufacturing conditions and various parameter values ​​are shown in Tables 1 and 2.

[0079] (Examples (E1-1) to (E1-4)) Laminated sheets (L1-1) to (L1-4) were obtained in the same manner as in Example (EV1-1) or (EV1-2), except that at least a portion (30 mass%, 50 mass%, or 100 mass%) of the base layer material was replaced with the pulverized laminated sheet (LV1-1) or (LV1-2) as a rework material. The main manufacturing conditions and various parameter values ​​are shown in Table 3. The virgin methacrylic resin (M) and the rework material were mixed by dry blending. The same applies to the other examples.

[0080] (Examples (E2-1), (E3-1)) Laminated sheets (L2-1) and (L3-1) were obtained in the same manner as in Example (EV2-1) or (EV3-1), except that a part (50 mass%) of the base layer material was replaced with the pulverized laminated sheet (LV2-1) or (LV3-1) as a rework material. The main manufacturing conditions and various parameter values ​​are shown in Table 3.

[0081] (Comparative example (EC11-1)~(EC11-4)) Laminated sheets (LC11-1) to (LC11-4) were obtained in the same manner as in Comparative Example (ECV11-1) or (ECV11-2), except that at least a portion (30 mass%, 50 mass%, or 100 mass%) of the base layer material was replaced with the pulverized laminated sheet (LCV11-1) or (LCV11-2) as a rework material. The main manufacturing conditions and various parameter values ​​are shown in Table 4.

[0082] [Evaluation Results] The evaluation results are shown in Tables 1 to 4.

[0083] [Table 1]

[0084] [Table 2]

[0085] [Table 3]

[0086] [Table 4]

[0087] [Summary of results] In Examples (EV1-1) to (EV3-1) and (EV1-2), when gradient high performance liquid chromatography (gradient HPLC) analysis was performed using two liquids, n-hexane and chloroform, as the eluent, an acrylonitrile-styrene copolymer (AS-E) was used as the styrene copolymer (S), in which the ratio of copolymers having a composition with an elution time of 9 minutes or less was 0 to 5 mass%, the ratio of copolymers having a composition with an elution time of 23 minutes or more was 0 to 5 mass%, and the elution time of the peak top of the maximum peak in the chromatogram was 9 to 23 minutes. In these Examples, a laminate sheet was produced in which a substrate layer containing a methacrylic resin (M) and a surface layer containing an acrylonitrile-styrene copolymer (AS-E) were laminated on both sides of the substrate layer, using only virgin materials as the materials for the substrate layer and the surface layer. All of the laminate sheets obtained in these Examples had good ink adhesion and laser cutting processability, a haze value of 1% or less, and good transparency.

[0088] In Examples (E1-1) to (E1-4), laminate sheets were obtained in the same manner as in Examples (EV1-1) or (EV1-2), except that 30 to 100% by mass of the total raw material of the base layer was replaced with a rework material made of the pulverized laminate sheet (LV1-1) or (LV1-2). All of the obtained laminate sheets had good ink adhesion and laser cutting processability, a haze value of 1% or less, and good transparency. In these examples, the compatibility between the acrylonitrile-styrene copolymer (AS-E) and the methacrylic resin (M) used was good, and even when a large amount of rework material was used, a high-quality laminate sheet was obtained as in the examples using only virgin material. In these examples, a laminate sheet with excellent sustainability including the rework material was obtained. Similar results were obtained in Examples (E2-1) and (E3-1).

[0089] In the comparative examples (ECV11-1) and (ECV11-2), a comparative acrylonitrile-styrene copolymer (ASC) was used as the styrene copolymer (S), in which the ratio of copolymers having a composition with an elution time of 23 minutes or more was more than 5% by mass when gradient high performance liquid chromatography (gradient HPLC) analysis was performed using two liquids, n-hexane and chloroform, as the eluent. In these comparative examples, a laminate sheet was produced in which a substrate layer containing a methacrylic resin (M) and a surface layer containing a comparative acrylonitrile-styrene copolymer (ASC) were laminated on both sides of the substrate layer, using only virgin materials as the materials for the substrate layer and the surface layer. All of the laminate sheets obtained in these examples had good ink adhesion and laser cutting processability, a haze value of 1% or less, and good transparency.

[0090] In Comparative Examples (EC11-1) to (EC11-4), laminate sheets were obtained in the same manner as in Comparative Example (ECV11-1) or (ECV11-2), except that 30 to 100% by mass of the total raw material of the base layer was replaced with a rework material made of the pulverized laminate sheet (LCV11-1) or (LCV11-2). The haze value of each of the obtained laminate sheets was extremely high at 4.7 to 15.6%, and the transparency was poor. In these examples, the compatibility between the styrene-based copolymer (S) and the methacrylic resin (M) used was poor, and a laminate sheet with excellent transparency and excellent sustainability was not obtained even if the rework material was included.

[0091] The present invention is not limited to the above-described embodiment and examples, and appropriate design changes are possible without departing from the spirit of the present invention. [Explanation of symbols]

[0092] 16X, 16Y laminated sheet 21 Base material layer 31, 32, 33 surface layer

Claims

1. A laminated sheet having a base layer and a surface layer laminated on at least one surface of the base layer, The base layer contains a methacrylic resin (M) containing 80 to 100% by mass of methyl methacrylate units, The surface layer is a laminate sheet containing an acrylonitrile-styrene copolymer (AS-E) in which, when gradient high performance liquid chromatography analysis is performed under the following conditions using two eluents, n-hexane and chloroform, the ratio of copolymers having a composition with an elution time of 9 minutes or less is 0 to 5 mass %, the ratio of copolymers having a composition with an elution time of 23 minutes or more is 0 to 5 mass %, and the elution time of the peak top of the maximum peak in a chromatogram is 9 to 23 minutes. <Conditions for gradient high performance liquid chromatography analysis> A silica gel column with an inner diameter of 4.6 mm and a length of 25 cm, packed with spherical fully porous silica gel with a particle size of 5 μm, is used. The column temperature is set to 40° C. A sample solution with a concentration of 0.5 mg / mL is prepared using chloroform as a solvent. When the time from the start of the analysis is T (minutes), the gradient profile of the mobile phase is as follows: The mobile phase between T=0 and T=5 is a mixed solution of n-hexane / chloroform (50 vol% / 50 vol%). Between T=5 and T=20, the chloroform concentration in the mobile phase is increased at a constant rate from 50 vol % to 100 vol %. The mobile phase between T=20 and T=25 is 100 vol% chloroform. The flow rate of the mobile phase is 0.8 mL / min. As a detector, an absorbance detector with a detection wavelength of 260 nm is used.

2. The maximum peak of the chromatogram of the acrylonitrile-styrene copolymer (AS-E) has a peak top elution time of 15 to 22 minutes, and the peak width (W 0.05h 2. The laminate sheet according to claim 1, wherein the symmetry coefficient (S) measured in accordance with JIS K0124 is 1.2 to 3.

4.

3. 2. The laminate sheet according to claim 1, wherein the average styrene monomer unit concentration in the entire laminate sheet is 0.1 to 20% by mass.

4. 2. The laminate sheet according to claim 1, wherein the base layer is made of a methacrylic resin composition (MR) containing a methacrylic resin (M) and an acrylonitrile-styrene copolymer (AS-E).

5. 2. The laminate sheet according to claim 1, wherein the content of styrene-based monomer units in the constituent resin of the base layer is 0 to 10.0% by mass.

6. 6. The laminate sheet according to claim 5, wherein the content of styrene-based monomer units in the constituent resin of the base layer is 1.2 to 10.0 mass %.

7. The laminate sheet according to claim 4, wherein at least a portion of the total raw materials of the base layer is a recycled resin composition (R) consisting of crushed material of the laminate sheet produced in the past or a processed product of the crushed material.

8. The laminate sheet according to claim 1, wherein the total thickness of the laminate sheet is 1 to 10 mm.

9. 2. The laminate sheet according to claim 1, which is adapted for inkjet printing and / or laser cutting.

10. The laminate sheet of claim 1 which is a coextruded sheet.

11. A printed matter, obtained by inkjet printing on the surface layer of the laminate sheet according to claim 1.

12. A molded article obtained by subjecting the laminate sheet according to claim 1 to inkjet printing and laser cutting.

13. 5. The method for producing a laminate sheet according to claim 4, wherein the laminate sheet is co-extruded using a recycled resin composition (R) consisting of crushed material of the laminate sheet produced in the past or a processed product of the crushed material as at least a part of the total raw material of the base layer.

Citation Information

Patent Citations

  • Thermoplastic-resin multilayer structure

    JP1984012850A

  • Antistatic multilayer sheet and antistatic thermoformed article

    JP2008221839A

  • Heat-shrinkable multi-layer film

    JP2009285892A

  • A multilayer optical film layer containing a blend of methyl methacrylate polymer and styrene acrylonitrile polymer.

    JP2011528450A

  • Laminate and novelty goods

    JP2021160119A